GALECTIN-1 AND ITS ROLE IN DEVELOPMENT OF INNATE AND ADAPTIVE IMMUNITY - V. D. Yakushina (SPb RAACI, 2014)
Abstract. Galectins comprise a family of β-galactoside-binding animal proteins, which are defined bycommon homologies of their carbohydrate-recognizing domaine (affinity for poly-N-acetyllactosamine). These lectins bind to cell surface glycans and extracellular matrix, thus influencing various cellular events, including cell cycle, adhesion, migration, proliferation and apoptosis. Moreover, galectins are able to exert intracellular effects, and participate, e.g., in signal transduction, by interacting with other nuclear and cytoplasmic proteins. Galectin-1 is considered to play a special role in functional regulation of immune cell activity. Thus protein is a factor of immunocompetent cell cooperation, thus being able to modulate immune reactions. In this respect, galectin-1 is considered as a potential agent or a target for new methods aimed to correct pathological processes associated with imbalance of immune system. This article provides an overview of works devoted to a possible role of galectin-1 in development of typical features of innate and adaptive immunity.